Evaluation of preloaded intraocular lens injection systems: Ex vivo study. Issue 4 (April 2017) - Nanavaty, Mayank A.; Kubrak‐Kisza, Magdalena
Abstract : Purpose : To compare preloaded intraocular lens (IOL) injection systems. Setting : Sussex Eye Hospital, Brighton, United Kingdom. Design : Experimental study. Methods : In 30 porcine eyes, 5 preloaded +22.0 diopters IOLs were implanted from each of the following preloaded IOL systems: Ultrasert (U), iTec (iT), Eyecee (E), iSert (iS), Rayone (R), and CT Lucia (CT). External and internal wound size was measured. Nozzle damage was assessed using digital photography. The ease of opening the pack, ophthalmic viscosurgical device (OVD) injection, advancing into the nozzle, nozzle insertion, and IOL delivery was scored on a 4‐point Likert scale, and the time was recorded. Results : The iT, E, and iS injectors with acute angled bevels and shorter nozzle tips showed more damage after implantation. The fastest with regard to opening the pack and nozzle insertion was U, OVD injection and advancing into the nozzle was E, and IOL delivery was R. The maximum postimplantation wound stretch was 20% with the CT (mean 2.64 mm ± 0.1 [SD]), and the least was 11.8% with the iT (mean 2.46 ± 0.1 mm). Both the U and R scored 4 (very easy) for all parameters measured; the E, iS, iT, and CT scored 4 or less in some parameters with decreasing scores, respectively. Conclusions : The models, design, and injection systems varied with each brand; however, the longer and more parallel the nozzle and less acute the angle of the bevel tip, the lesser the stress with less nozzle damage after surgery. All preloaded systems varied in the ease‐of‐use and time for surgical steps, and all lead to postoperative wound stretch.